KONSELING ISLAM SEBAGAI SOLUSI FENOMENA TRANSGENDER - Mu'adil Faizin (Nizham Jurnal Studi Keislaman, 2016)
The transgender phenomenaon in Indonesia is known as an undesirable group of people, furthermore getting backbitting. Clearly, Islam avoids the undesirable. Finally, transgender people become a minority of people and getting different dos. Consequently, the researcher discusses Islamic Conseling As The Solution Of Transgender Phenomenaon. The research is library research which uses the analysis method to content analysis. The research discovers that transgender were considered mentally ill simply. Many transgender people have reported incidence of depression varies and become signiﬁcantly higher levels of suicidality. In the psychological knowledge, Spritual intervention is the most of urgent ways to cure mental illness, so that islamic conseling as the solution of transgender phenomenaon could be done with several steps; the first, giving them knowledge about self-convidence; the second, insisting fundamental Islamic belief; the third, letting them approach to Allah SWT; the fourth, giving them knowledge about Islamic law of transgender phenomenon.